2014
DOI: 10.1111/1460-6984.12129
|View full text |Cite
|
Sign up to set email alerts
|

Maternal responsiveness predicts child language at ages 3 and 4 in a community‐based sample of slow‐to‐talk toddlers

Abstract: Slow-to-talk toddlers of mothers with higher global ratings of responsiveness have higher language scores at 3 and 4 years of age. This global measure of maternal responsiveness could be further developed as a clinical tool for identifying which slow-to-talk toddlers are most in need of early intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 30 publications
3
38
0
1
Order By: Relevance
“…In comparison to task performance, language development of young children is probably more dependent on family factors such as socioeconomic status and maternal responsiveness (23,24). If maternal hypothyroxinaemia is associated with socio economic status, or its indicators (Table 2), and this in turn with language test score, it would explain why the relation between hypothyroxinaemia and poor language test score disappeared after statistical correction for the family background.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to task performance, language development of young children is probably more dependent on family factors such as socioeconomic status and maternal responsiveness (23,24). If maternal hypothyroxinaemia is associated with socio economic status, or its indicators (Table 2), and this in turn with language test score, it would explain why the relation between hypothyroxinaemia and poor language test score disappeared after statistical correction for the family background.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that word frequency, grammatical complexity, and gender differences in language input influence early vocabulary size and growth (Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991;Snow, 1972). In a similar way, several dimensions of maternal responsiveness predict children's acquisition of language milestones as early as 9 months of age (Tamis-LeMonda, Bornstein, & Baumwell, 2001) and even into the fourth year of life (Hudson, Levickis, Down, Nicholls, & Wake, 2015). Qualitative aspects of language exposure have been much less studied in the bilingual literature.…”
Section: Effects Of Quantity and Quality Of Language Exposure In Bilimentioning
confidence: 99%
“…Responsiveness, that is, the adaptation of the language support to the language skills of the child, is important. Children of very responsive mothers were proven to have better language skills (Hudson, Levickis, Down, Nicholls, & Wake, 2015). In very young children, parents are usually the appropriate starting point for an intervention.…”
Section: Introductionmentioning
confidence: 99%